Pemanfaatan Aplikasi Mindjet Mindmanager dalam Meningkatkan Literasi Materi Pembelajaran IPS - Nurleli Ramli; Amiruddin Mustam (JINoP (Jurnal Inovasi Pembelajaran), 2022)
The online learning system has an impact on student learning patterns, especially when the lecturer only assigns students to answer questions that do not require them to be skilled in thinking as a result, students do not understand the learning material and indicate that they are only at the performative and functional literacy level. This study aims to find out how the use of the Mindjet Mindmanager application can be used as a medium to improve student literacy in social sciences learning materials. The study used a quantitative descriptive method with 35 respondents from Tadris IPS IAIN Parepare students in the first semester. The results showed that the literacy level of Tadris IPS IAIN Parepare students changed with the difference between the pre-test and post-test items for performative items 2.14, functional 0.69, informational 4.77, and epistemic 3.4. This is because the mindjet mindmanager application requires students to find keywords from what they read and connect one concept to another in describing a topic of social sciens learning materials.